ANALISIS INDIKASI PENYALAHGUNAAN BELANJA HIBAH OLEH PASLON INCUMBENT PADA PEMILUKADA SERENTAK 2020 - Tanjung, Abdul Hafiz; Alamsyah, Salma Rizkiyanti (AKUNTANSI DEWANTARA, 2023)
The purpose of this study was to examine the tendencies to abuse the power of incumbent candidates in making budget of grant expenditure to support their political interests in the local election on December 9th,2020, in Indonesia. Sample were chosen by random sampling with proporsional allocation between district and municipals. The sample for the first population was 56 district/municipals, consisting 51 district and 5 municipalities, while the sample for the second population was 57 district/municipals, consisting of 46 district and 11 municipalities. Two statistical analysis were used in this research; the first was Wilcoxon signed rank test and the second was the Mann-Whitney U test. Data normality test using kanji w/s test had been done to determine which analysis to be used. The result of hypothesis test have been tested at confidence 95% and showed that there was a significant increase in mean log of incumbent candidates in the year 2019 compared to 2020, while for the mean log of grant expenditure for incumbent candidates and non-incumbent candidates at the time of the local election (2020) there was a significant difference